2009
DOI: 10.12800/ccd.v4i12.146
|View full text |Cite
|
Sign up to set email alerts
|

Características y efectos de los métodos resistidos en el sprint. (Characteristics and effects of resisted sprint training methods)

Abstract: ResumenPara la mejora del rendimiento en el sprint se utilizan distintos métodos de entrenamiento, entre los más populares se encuentran los métodos resistidos. Un método resistido para el sprint se caracteriza por utilizar sprints con una sobrecarga o resistencia añadi-da. Dependiendo de las características del dispositivo, tanto la magnitud como la dirección de la resistencia va a ser diferente. Así, existen distintos tipos de méto-dos resistidos, estos son: arrastres de trineos o ruedas, lastres de chalecos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
3
0
2
Order By: Relevance
“…This aspect conditions the internal load imposed on the athlete and, therefore, the adaptations that occur in one direction or another. Thus, there is a need for research in this area 30 . Finally, it should be noted that two of the studies included in the meta-analysis were conducted with U-19 soccer players.…”
Section: Linear Sprint Timementioning
confidence: 99%
See 1 more Smart Citation
“…This aspect conditions the internal load imposed on the athlete and, therefore, the adaptations that occur in one direction or another. Thus, there is a need for research in this area 30 . Finally, it should be noted that two of the studies included in the meta-analysis were conducted with U-19 soccer players.…”
Section: Linear Sprint Timementioning
confidence: 99%
“…It is well known that RST training could be instrumental in improving these physical attributes, especially concerning sprint acceleration and maximal velocity 24,25,28 . In the current scientific literature, research has been conducted on athletes with other tools such as parachutes or hills [29][30][31] , but there is a lack of knowledge in the field of soccer. Indeed, recent studies have indicated the efficacy of RST in improving various physical performance metrics, such as sprint performance, jumping, and strength [32][33][34] .…”
Section: Introductionmentioning
confidence: 99%
“…Current research supports the bene ts of moderate loads, though consensus on the optimal load is lacking (24). Commonly, a reduction in peak speed by no more than 10% is accepted as an appropriate load standard (16, 19), a notion supported by expert opinions rather than scienti c evidence, as noted by tness experts like Alcaraz et al (32). Given the in uence of different surface frictions, there is a gap in…”
Section: Introductionmentioning
confidence: 99%
“…En este tipo de entrenamiento es recomendable ejecutar las repeticiones a la máxima velocidad posible y con la mínima pérdida de velocidad en cada serie (González Badillo & Ribas-Serna, 2019). Si bien seguimos el principio de especificidad, deberemos imitar la activación muscular y la velocidad de ejecución de los movimientos propios de la disciplina deportiva (Alcaraz et al, 2009).…”
Section: Introductionunclassified